The impact of comorbidities on the length of hospital stay after coronary artery bypass grafting - Vučković, Andrea; Đurić, Katarina; Filipović, Marko; Tasić, Danijela; Tasić, Nebojša (Medicinski podmladak, 2025)
ABSTRACT Introduction: Ischemic heart disease is one of the leading causes of death worldwide and occurs as a result of an imbalance between the myocardium’s oxygen demand and its blood supply. The most common cause of ischemic heart disease is atherosclerosis of the coronary arteries. The main methods of treatment include myocardial revascularization through coronary artery bypass grafting or percutaneous coronary intervention, as well as pharmacological therapy. Aim: The aim of this study is to analyze the impact of comorbidities, lifestyle habits, and heredity on the length of hospitalization after aortocoronary bypass grafting. Material and methods: Data for this study were obtained from medical records of patients operated at the Institute for Cardiovascular Diseases Dedinje from November 30th, 2022 to January 19th, 2023. This is a descriptive epidemiological study. Statistical analysis was performed using SPSS 21.0 software. Results: A total of 106 patients were operated on from November 30th, 2022 to January 19th, 2023, of whom 76 (71.7%) were male. The median age of patients was 66 (range 39-78) years. Patients who underwent simultaneous valve and bypass surgery were statistically significantly longer hospitalized than those who did not undergo valve surgery (p=0.008). The research results indicate that age (p=0.001) and NYHA class of heart failure (p=0.006) are statistically significantly positively correlated with the length of hospitalization. The presence of other comorbidities, hereditary burden, and smoking, in this study, was not statistically significantly associated with the length of hospitalization after aortocoronary bypass grafting (p>0.05). Conclusion: The practical application of the results of this study lies in the ability to predict the length of hospitalization based on the presence of certain comorbidities, advanced heart failure, valve surgery, and patient age.